Peran Strategi Forum Kerukunan Umat Beragama (FKUB) Wilayah Sulawesi Selatan dalam Mewujudkan Persatuan dan Keutuhan Bangsa - Natsir, Muh.; Ridha, Muhammad (Sulesana, 2023)
The Religious Harmony Forum (FKUB) is a forum formed on community ideas facilitated by the Government with the aim of maintaining, building and empowering religious communities for the sake of harmony and prosperity. South Sulawesi as a province that is multicultural and multi-religious makes each region in it prone to conflicts between groups. This study aims to see the extent of the role of FKUB in South Sulawesi in realizing the unity and integrity of the nation. This type of research is field research which aims to obtain data, both primary and by direct tracing each area in South Sulawesi, especially those experiencing inter-religious conflicts by conducting in-depth interviews with FKUB administrators. South Sulawesi, district/city FKUB, Local Government in this case the National and Political Unity Agency (kesbangpol), Ministry of Religion, and of course indigenous peoples. while secondary data as supporting data was obtained through the central management group of FKUB South Sulawesi. The results show that the status of religious harmony in South Sulawesi is still high. This is supported by the index value of religious harmony studied by the Ministry of Religion with a score of 75.7 (high category). FKUB's strategy in mediating inter-religious conflicts in South Sulawesi is to prioritize dialogue, deliberation and opinion polls. The high awareness of the majority of South Sulawesi residents in terms of tolerance, equality and cooperation between fellow religious adherents supports the South Sulawesi FKUB in an ef ort to realize the unity and integrity of the nation.